Partisipasi pemangku kepentingan dalam pengelolaan perikanan darat berbasis ekosistem di rawa blorep kabupaten Merauke - Situmorang, Gita Grhichia; Amir, Astaman; Pakidi, Chalvyn Silasa (AGRICOLA, 2024)
Blorep Swamp is one of the swamps in Merauke Regency, with the status of a swamp being City Forest. Blorep Swamp is one of the swamps that has enormous potential for fish resources and can provide a decent life for the people living around Blorep Swamp. This study aims to analyze the social conditions of the community in ecosystem-based inland fisheries management (EAFM), where the indicators used include stakeholder participation. The time of the research was carried out from March to May 2023. The data collection method used observation, interview and documentation techniques. The results showed that the social condition of the community in the management of Blorep Swamp on the stakeholder indicator was at a low status, this was because the existence of Blorep Swamp could be said to be very secretive which resulted in several government agencies not knowing the existence of the swamp. Meanwhile, the indicators of fisheries conflict and utilization of local knowledge are in good status.